The 17‐gene stemness score associates with relapse risk and long‐term outcomes following allogeneic haematopoietic cell transplantation in acute myeloid leukaemia. Issue 3 (23rd May 2022) - Kim, Dennis D. H.; Novitzky Basso, Igor; Kim, Taehyung Simon; Yi, Seong Yoon; Kim, Kyoung Ha; Murphy, Tracy; Chan, Steven; Minden, Mark; Pasic, Ivan; Lam, Wilson; Law, Arjun; Michelis, Fotios V.; et al.
Abstract: A 17‐gene stemness (LSC17) score determines risk in acute myeloid leukaemia patients treated with standard chemotherapy regimens. The present study further analysed the impact of the LSC17 score at diagnosis on outcomes following allogeneic haematopoietic cell transplantation (HCT). Out of 452 patients with available LSC17 score, 123 patients received allogeneic HCT. Transplant outcomes, including overall (OS), leukaemia‐free survival (LFS), relapse incidence (RI) and non‐relapse mortality (NRM), were compared according to the LSC17 scored group. The patients with a low LSC17 score had higher OS (56.2%) and LFS (54.4%) at 2 years compared to patients with high LSC17 score (47.2%, p = 0.0237 for OS and 46.0%, p = 0.0181 for LFS). The low LSC17 score group also had a lower relapse rate at 2 years (12.7%) compared to 25.3% in the high LSC17 score group ( p = 0.017), but no difference in NRM ( p = 0.674). Worse outcomes in the high LSC17 score group for OS, LFS and relapse were consistently observed across all stratified sub‐groups. The use of more intensive conditioning did not improve outcomes for either group. In contrast, chronic graft‐versus‐host‐disease was associated with more favourable outcomes in both groups. The 17‐gene stemness score is highly prognostic for survival and relapse risk following allogeneic HCT.